Economic Analysis of Cost of Cultivation and Benefit Cost Ratio of Cauliflower in Response to Solid and Liquid Organic Mannure - Chawla, Gajendra; Hariyana, Kuldeep; Khan, Salman; Tetarwal, Pooja; Rathore, Pooja; Meena, Deshraj (International Journal of Environment, Agriculture and Biotechnology, 2024)
This study evaluates the economic impact of using solid and liquid organic manures on the cultivation of cauliflower, focusing on the cost of cultivation and the benefit-cost (B:C) ratio. The experiment was conducted at technology park CTAE, MPUAT, Udaipur during Rabi season 2021-22 under controlled conditions, where different treatments involving sole and combined application of organic manures (FYM and vermicompost) and four levels of panchagavya were evaluated on cauliflower crop with three replications under factorial RBD design. The analysis involved calculating the total cost of cultivation, including inputs, labour, and other variable costs, and comparing these costs with the net returns obtained from the crop yield. The B ratio was then determined to assess the profitability of each treatment. Result showed that among organic manures application of OM3 treatment (50% RDN through FYM and 50% RDN through vermicompost) as soil application was found recorded maximum net return of Rs. 174791.08. Among different levels of panchagavya, application at 5% concentration as foliar spray gave maximum net return of Rs. 164587.74. The interactive effect of organic manures and panchagavya on net return showed that the combined application of OM3 + PG2 (50 per cent FYM + 50 per cent RDN through Vermicompost + 5 per cent Panchagavya) gave maximum net return of Rs. 206075.16 from cauliflower crop and The combined effect of organic manures and panchagavya on B:C ratio showed that the combined application of OM0 + PG2 (control + 5 per cent Panchagavya) gave maximum B:C ratio of 2.90.